Hovering efficiency optimization of the ducted propeller with weight penalty taken into account - Hu, Yu; Qing, Ji xiang; Liu, Zhong Huan; Conrad, Zachary J.; Cao, Jia Ning; Zhang, Xue Peng (Aerospace science and technology, 2021)
The ducted propeller is superior to the open propeller in hovering efficiency. However, the overall system efficiency of a ducted propeller is reduced due to its heavy structure. If the weight penalty is taken into account, will the ducted propeller still be superior to an open propeller? And in this scenario, how will a ducted propeller with better efficiency than an open propeller be designed? This paper investigates these questions by parametric analysis based on experiments and then parametric optimization that involves hovering efficiency and structural weight in objective functions. Both multi-disciplinary design optimization and multi-objective programming are performed by surrogate-based optimization. An in-house automatic structured mesh generation module is developed to deal with significant geometry variation in design space. Finally, the optimization results are validated by post-optimization experiments. The results of experiment and optimization indicate that the effects of weight penalty play a leading role at low disk loading and hence in this case, the one with lighter structure is superior. But at high disk loading, as thrust gets higher, the leading factor turns into aerodynamic hovering efficiency, therefore the one with higher aerodynamic hovering efficiency prevails. The multi-objective optimization produces an L-shaped Pareto front, and the optimum of multi-disciplinary optimization is quite close to the Pareto front knee point. The designs in this region encounter limited aerodynamic hovering efficiency loss but gain significant weight reduction. Therefore, we can obtain a ducted propeller superior to an open propeller in system efficiency with pretty low disk loading, although the weight penalty is considered. These designs feature a relatively large inner lip radius, a small outer lip radius, and a short or even no diffuser. This means that the inner lip radius contributes the most to the aerodynamic hovering efficiency, followed by the diffuser and outer lip. These designs have very low height to diameter ratio therefore they can be easily integrated into aircraft structure.